2022
DOI: 10.3390/ijerph19063475
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable Mortality between Metropolitan and Non-Metropolitan Areas in Korea from 1995 to 2019: A Descriptive Study of Implications for the National Healthcare Policy

Abstract: This study aims to investigate the trends of avoidable mortality and regional inequality from 1995 to 2019 and to provide evidence for policy effectiveness to address regional health disparities in Korea. Mortality and population data were obtained from the Statistics Korea database. Age-standardized all-cause, avoidable, preventable, and treatable mortality was calculated for each year by sex and region. Changes in mortality trends between metropolitan and non-metropolitan areas were compared with absolute an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Previous research examining the increase in LE between 1998 and 2017 revealed that a major driver of the increase in LE was the decline in avoidable mortality from diseases such as cardiovascular diseases, neoplasms, and transport injuries [16]. The decrease in avoidable mortality was faster than that of all-cause mortality in Korea, and the rate of decrease was more prominent in RAs than in LUAs or SMUAs [4,5]. This study found that faster increases in RAs and SMUAs enhanced the overall increase in LE in Korea than in LUAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research examining the increase in LE between 1998 and 2017 revealed that a major driver of the increase in LE was the decline in avoidable mortality from diseases such as cardiovascular diseases, neoplasms, and transport injuries [16]. The decrease in avoidable mortality was faster than that of all-cause mortality in Korea, and the rate of decrease was more prominent in RAs than in LUAs or SMUAs [4,5]. This study found that faster increases in RAs and SMUAs enhanced the overall increase in LE in Korea than in LUAs.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidable mortality rate decreased more rapidly, by 63.5% in urban areas and 61.6% in rural areas. The expansion of a centralized healthcare policy, improvement in material living standards in rural areas, and a special budget for areas with poor health and medical facilities were all nominated as causes of a similar relative decrease in mortality in urban and rural areas [5]. Further research is required to determine which policy factors or processes causally contribute to this decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the ninth lowest among the Organization for Economic Cooperation and Development (OECD) countries, and the country with the largest mortality rate decrease was Korea, which decreased from 1075.6 per 100,000 persons to 44.7% in 2001. 1) …”
mentioning
confidence: 99%
“…In addition, the level of health behaviors such as smoking rate and the risk of chronic diseases such as obesity were high in non-metropolitan areas. 1) To address these issues, universal health coverage has been established and local public health policies have been strengthened over the past 30 years. 3) However, despite policy efforts to alleviate regional imbalances, its effectiveness is still unclear.…”
mentioning
confidence: 99%